Pharmacokinetics, safety and tolerability of OBE022, a selective prostaglandin F2α receptor antagonist tocolytic: A first‐in‐human trial in healthy postmenopausal women. (5th June 2018) - Pohl, Oliver; Marchand, Line; Gotteland, Jean‐Pierre; Coates, Simon; Täubel, Jörg; Lorch, Ulrike
Abstract : Aims: Preterm birth remains a significant risk for later disability. The selective inhibition of the prostaglandin F2α receptor has significant advantages for a tocolytic. The prodrug OBE022 and its metabolite OBE002 are novel prostaglandin F2α receptor antagonists under development for treating preterm labour. Methods: We performed a prospective, first in human, Phase I, dose escalation, placebo‐controlled, randomized trial at a clinical trial site in the UK. Placebo, single ascending doses of 10, 30, 100, 300, 1000 or 1300 mg, and multiple ascending doses over 7 days of 100, 300 or 1000 mg day –1 ; were administered to postmenopausal female volunteers. Food interaction was additionally evaluated. Results: Subjects tolerated OBE022 well at all single and multiple doses. No clinically relevant changes in safety parameters were shown and there were no serious adverse events. Observations showed that prodrug OBE022 was readily absorbed and rapidly converted into its equally active stable metabolite OBE002. The plasma level of OBE002 rose with increasing doses, reaching exposure levels that were anticipated to be clinically relevant within 1 h following administration. There was no clinically significant food interaction, with peak exposures reduced to 80% and area under the curve staying bioequivalent. The mean half‐life of OBE002 ranged between 8 and 11 h following administration of a single dose and 22–29 h after multiple doses. Conclusions: Administration of OBE022 was safe and had favourable pharmacokinetic characteristics and no clinically relevant interaction with food. Our results allow further investigation of OBE022 in preterm labour patients.